The evolution of the Uralian orogen - Puchkov V.N. (My University, 2009)
The Uralian orogen is located along the western flank of a huge (>4000 km long) intracontinental Uralo-Mongolian mobile belt. The orogen developed mainly between the Late Devonian and the Late Permian, with a brief resumption of orogenic activity in the Lower Jurassic and Pliocene–Quaternary time. Although its evolution is commonly related to the Variscides of Western Europe, its very distinctive features argue against a simple geodynamic connection. To a first order, the evolution of Uralian orogen shows similarities with the ‘Wilson cycle’, beginning with epi-continental rifting (Late Cambrian–Lower Ordovician) followed by passive margin (since Middle Ordovician) development, onset of subduction and arc-related magmatism (Late Ordovician) followed by arc–continent collision (Late Devonian in the south and Early Carboniferous in the north) and continent–continent collision (beginning in the mid-Carboniferous). In detail, however, the Uralides preserve a number of rare features. Oceanic (Ordovician to Lower Devonian) and island–arc (Ordovician to Lower Carboniferous) complexes are particularly well preserved as is the foreland belt in the Southern Urals, which exhibits very limited shortening of deformed Mesoproterozoic to Permian sediments. Geophysical studies indicate the presence of ‘cold’, isostatically equilibrated root. Other characteristic features include a Silurian platinum-rich belt of subduction-related layered plutons, a simultaneous development of orogenic and rift-related magmatism, a succession of collisions that are both diachronous and oblique, and a single dominant stage of transpressive deformation after the Early Carboniferous. The end result is a pronounced bi-vergent structure. The Uralides are also characterized by Meso-Cenozoic post-orogenic stage and plume-related tectonics in Ordovician, Devonian and especially Triassic time. The evolution of the Uralides is consistent with the development and destruction of a Palaeouralian ocean to form part of a giant Uralo-Mongolian orogen, which involved an interaction of cratonic Baltica and Siberia with a young and rheologically weak Kazakhstanian continent. The Uralides are characterized by protracted and recurrent orogenesis, interrupted in the Triassic by tectonothermal activity associated with the Uralo-Siberian superplume.
Keywords: Urals